THE EFFECT OF COOPERATIVE LEARNING MODEL THROUGH THE JIGSAW METHOD ON CRITICAL THINGKING ABILITY AND INCREASING STUDENT LEARNING ACHIEVEMENT IN LEARNING OF CIVICS AT SMAN 4 MADIUN ACADEMI YEARS 2022/2023 - Yati, Panca Budi; Nuswantari, Nuswantari; Mustakarini, Indriyana Dwi; Harmawati, Yuni (JURNAL SETIA PANCASILA, 2023)
This study aims to determine the effect of the cooperative learning model through the jigsaw method on critical thinking skills and increasing student achievement in Civics learning at SMAN 4 Madiun City. The data used is primary data in the form of lesson plans; tests of critical thinking skills and increased student achievement. The population of this study were all students of class XI.2 as a class with the jigsaw cooperative learning model and X1.4 as the ordinary learning mode class, which totaled 60 students. The sampling technique used random sampling technique. Data analysis technique using independent sample t test. Data is processed using IBM SPSS Statistics v.18. The results showed that the cooperative learning model through the jigsaw method had an effect on critical thinking skills in Civics learning at SMAN 4 Madiun City, and the cooperative learning model through the jigsaw method had an effect on increasing student achievement in Civics learning at SMAN 4 Madiun City.